Using Retroviral Iterative Genetic Algorithm to Solve Constraint Global Optimization Problems - Moreira, Renato Simões; Teixeira, Otávio Noura; Lobato, Walter Avelino da Luz; Yanaguibashi, Hitoshi Seki; Oliveira, Roberto Célio Limão de (IntechOpen, 2012)
None